Perbedaan Self-Regulated Learning Pada Siswa Kelas Internasional dengan Siswa Kelas Reguler di SMA Shafiyyatul Amaliyah Medan - Siregar, Farida Hanum; Perangin-Angin, Agistha Fanessya (Granada El-Fath, 2021)
Method used in this research is the comparative method. The population in this study were all students of class X and XI SMA Shafiyyatul Amaliyah, namely 210 students. International class with a total of 30 in the regular class with a total of 180 students. The number of samples is 60 samples, 30 from the international class and 30 from the regular class. The technique used in sampling the two sample groups is the random sampling technique, meaning that all members in the population have the same opportunity to be selected as samples. Based on the calculation results of theanalysis t-test, it is known that there are differences in self-regulated learning between international class students and students in regular classes. This result is known by looking at the value or coefficient of difference in the ttest of 5.652 with a significance of 0.000 (p